THE PREVALENCE OF OCCLUSION CLASSIFICATIONS OF PERMANENT DENTITION IN TEHRAN'S STUDENTS AGED 12 To 13 YEARS - A Jafari; A Kowsari; J Mahmoodian; A Zrehgar (Acta Medica Iranica, 2008)
Classification of occlusion is the first step in diagnosing the relationship between the upper and lower jaw's teeth. Based on Angle's classification, occlusion is divided into three categories: class I, class II, and class III. The aim of this study was to determine the prevalence of occlusion categories, based on Angle's classification, in adolescents with permanent dentition in Tehran. This is an epidemiological cross sectional, randomized and descriptive study. Based on minimum rate of prevalence belonging to class III, number of cases was calculated and 1524 students, equal boys and girls, were studied. The prevalence of each classification in boys, girls and in total was determined. Among all cases, 79% were in class I occlusion; about 14.5% were in class II and 6.5% in class III. From Angle's 1899 study of prevalence of occlusion type until now, many studies have been done with different results. It seems that prevalence of occlusion type strongly depends on genetic factors and area of the study.